Effect of Bono de Desarrollo Humano (Conditional Cash Transfer 1 Programme) on childhood mortality: a nationwide analysis of 2 Ecuadorian counties - Granizo Mena, Guillermo Vinicio (2018)
Background: The mortality rate in children under five years old (U5MR) has decreased 24 considerably in Ecuador; however, thousands of children continue to die from causes 25 related to poverty. A social program known as Bono de Desarrollo Humano (BDH) was 26 created to guarantee a minimum level of consumption for families and to reduce chronic 27 malnutrition and preventable and preventable childhood diseases. 28 Objective: To evaluate the effect of the Bono de Desarrollo Humano programme on 29 mortality of children younger than 5 years, particularly from malnutrition, diarrheal 30 diseases, and lower respiratory tract infections. 31 Methods: Mortality rates and the BDH coverage from 2009 to 2014 was evaluated from 32 the 144 (of 222) Ecuadorian counties with intermediate and adequate quality of vital 33 information. A multivariable regression analyses for panel data was conducted by using 34 a negative binomial regression model with fixed effects, adjusted for relevant 35 demographic and socioeconomic covariates. 36 Results: For each 1% increase in BDH coverage, calculated from the county population 37 (CP) or the eligible population (EP), there would be a decrease in U5MR of 3% (RR 38 0.971, 95% CI 0.953-0.999) and 1.5% (RR 0.985, CI 0.973-0.998), respectively. A 39 lower effect of BDH on mortality resulting from respiratory infections was observed 40 (BDH-CP coverage: reduction of 0.8%, 95% CI 0.984-0.999 and BDH-PE coverage: 41 reduction of 0.5%, 95% CI 0.989-0.999). The BDH also reduced hospital discharge 42 rates in children younger than 5 years, resulting from all causes and for diarrhea. 43 Conclusion: 44 A conditional cash transfer program such as Bono de Desarrollo Humano could 45 contribute to the reduction of mortality due to causes related to poverty, such as 46 malnutrition and respiratory infections. Ecuador, being a country that has recently 47 3 increased the amount of the BDH, requires making a careful monitoring and evaluation 48 of the impact of the program to ensure that truly reduce inequities and improves health.